A Contrastive Analysis of Suffixes between English and Uzbek Languages - Sumiati Sumiati; Sherly Marliasari (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2018)
This study is about the contrastive analysis of suffixes in English and Uzbek languages. This study was done to find out the differences and similarities of suffixes in English and Uzbek languages and focused on form, function, and meaning. Technique for collecting data in this study is obtained from the documentation, including websites, journals, dictionaries and English and Uzbek morphology and grammar books. This research used the descriptive qualitative method. Contrastive analysis is used to describe the result of the study between English and Uzbek suffixes that had been compared. The result of research showed that there are five differences of suffixes in English and Uzbek in terms of their form, five differences in their function and six differences in their meaning. Also, there are three similarities of suffixes in English and Uzbek in terms of their form, six similarities in their function and three similarities in their meaning.